2015
DOI: 10.1091/mbc.e14-11-1552
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 1 controls the activation threshold of an α-arrestin by multisite phosphorylation of the interdomain hinge

Abstract: The yeast Rim8/Art9 α-arrestin, involved in ambient pH signaling, is regulated through multisite phosphorylation of the hinge region by the plasma membrane–associated casein kinase 1. This modification prevents its stable association with the pH sensor protein Rim21 at the plasma membrane and thereby inhibits signal transduction at acidic pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Therefore, analysis of CreA stability in creB and creD disruption mutant strains is necessary to understand the mechanism of CCR regulation in filamentous fungi. In yeast, phosphorylation of Art1 and Rim8/Art9 has been proposed to limit their association with the plasma membrane (28,30). Analysis of the subcellular localization of CreB and CreD will also augment our understanding of the target of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, analysis of CreA stability in creB and creD disruption mutant strains is necessary to understand the mechanism of CCR regulation in filamentous fungi. In yeast, phosphorylation of Art1 and Rim8/Art9 has been proposed to limit their association with the plasma membrane (28,30). Analysis of the subcellular localization of CreB and CreD will also augment our understanding of the target of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in lipid asymmetry and external alkalization may also cause some changes in Rim21 or other proteins of the Rim101 pathway. During preparation of this manuscript, it was reported that the activation threshold of the Rim101 pathway is regulated by phosphorylation of Rim8, a downstream molecule of Rim21 (40). Therefore, it is important that future investigations look at the relationship between Rim8 phosphorylation and how Rim21C associates with and dissociates from the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Herrador et al . have recently reported that the activity of yeast Rim8 (PalF) is antagonized by CK1‐mediated, Rim21‐dependent phosphorylation (Herrador et al, ). We have shown that PalH is phosphorylated in alkaline pH‐ and PalF‐dependent manner, raising the possibility that the same kinase that is recruited by the activated arrestin phosphorylates the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pioneering studies revealing the involvement of this pathway in systemic candidiasis (Davis et al, 2000), studies with ascomycetes as diverse as the Saccharomycotina Candida albicans (Nobile et al, 2008) and the Pezizomycotina A. nidulans (Bignell et al, 2005) and A. fumigatus (Bertuzzi et al, 2014) have uncovered its key involvement in the ability of these fungi to infect mammalian hosts. Overwhelming evidence indicates that, in ascomycetes, the pal/RIM pathway ambient pH sensor is a transmembrane protein denoted PalH in A. nidulans and Rim21p in S. cerevisiae (Herranz et al, 2005;Herv as-Aguilar et al, 2007;Galindo et al, 2012;Obara et al, 2012;Herrador et al, 2015). This pH sensor is the most appealing component of the pathway to serve as druggable target, although it would be unsuitable for infections caused by the basidiomycetes, for example, Cryptococcus neoformans, given that although the RIM pathway is involved in its pathogenicity (O'Meara et al, 2010;2013;, PalH/Rim21p (and their associated arrestin, see below) appear to be missing in basidiomycete lineage (Cervantes-Ch avez et al, 2010;Ost et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation